Numerical simulation of the blood flow through the coronary artery stenosis: Effects of varying eccentricity. (July 2022) - Timofeeva, Mariia; Ooi, Andrew; Poon, Eric K.W.; Barlis, Peter
Abstract: Blockages within arteries, called stenoses, are a common cause of coronary artery disease (CAD). Stenosis is a result of atherosclerotic plaque build-up limits blood flow and hence oxygen and nutrient supplies. Past studies on stenosed arterial flows often assumed stenosis to be axisymmetric in shape. However, medical imaging modalities have shown that stenoses in the coronary arteries are often asymmetric. To address it, an asymmetric stenosis is considered in the model which is based on common dimensions of the left anterior descending artery (LAD). The hemodynamic impacts are studied over a range of degrees of eccentricity ( DoE ) and degree of stenosis ( DoS ) . Blood flow within the artery is analyzed by solving the incompressible Navier-Stokes equations with both resting and hyperemic flow rates. The wall shear stress ( WSS ), oscillatory shear index ( OSI ) and fractional flow reserve ( FFR ) are calculated. The eccentricity makes the flow deflect away from the model's centerline. Behavior of the deflected flow is significantly altered downstream of the stenosis. Transverse dimension of the recirculation zone grows with increasing DoE, while its longitudinal dimension mainly depends on DoS . Eccentricity also contributes to the development of secondary flow distal to the stenosis. Such complex flow behavior contributes to a further pressure loss and hence a significant change in FFR (<0.8). Calculated WSS and OSI indicate that in actual eccentric stenotic LAD the asymmetric remodeling is anticipated. Thus, consideration of the DoE, along with the DoS, could lead to better patient stratification. Graphical abstract: Image 1 Highlights: Behavior of the deflected flow is significantly altered downstream of the eccentric stenosis. Eccentricity contributes to the development of secondary flow distal to the stenosis. Transverse dimension of the recirculation zone grows with increasing DoE, while its longitudinal dimension mainly depends on DoS. Complex flow behavior contributes to a further pressure loss and hence a significant change in FFR ‾ (<0.8). Calculated WSS ‾ and OSI indicate that in actual eccentric stenotic left anterior descending artery the asymmetric remodeling is anticipated.